Small Mirrors for Small Satellites: Design of the Deformable Mirror Demonstration Mission CubeSat (DeMi) Payload - Douglas, Ewan S.; Allan, Greg; Morgan, Rachel; Holden, Bobby G.; Gubner, Jennifer; Haughwout, Christian; do Vale Pereira, Paula; Xin, Yinzi; Merk, John; Cahoy, Kerri L. (Frontiers in Astronomy and Space Sciences, 2021)
The Deformable Mirror Demonstration Mission (DeMi) is a technology demonstration CubeSat to test a 140 actuator micro-electromechanical system (MEMS) deformable mirror in low-Earth orbit. Such mirrors can provide precise wavefront control while being low size, weight, and power. Hence, they have the potential of improving contrast in coronagraphs on future space telescopes. In the DeMi payload, a Shack Hartmann lenslet array based wavefront sensor monitors the deformable mirror, illuminated by either an internal 636 nm laser diode or external starlight. This work describes the instrument design drivers and CubeSat implementation, and briefly illustrates operation on orbit by comparing ground-based measurements of a displaced actuator to an on-orbit measurement using the internal laser source. The 6U CubeSat was launched on February 25th, 2020 and deployed from the International Space Station on July 13th, 2020.